Advancing road ecology in Africa with robust analyses and cautious inferences: a response to Jackson et al. (2017) - González-Suárez, Manuela; D'Amico, Marcello; Mulero-Pázmány, Margarita Cristina (The Zoological Society of London, 2017)
Jackson et al. (2017) have written an extensive commentary on our published study of ungulate behavioral responses to roads and traffic in South Africa (Mulero-Pázmány, D'Amico & González-Suárez, 2016). We welcome the opportunity to engage in discussion regarding road ecology in Africa and how to best assess impacts and interpret findings. We all agree that understanding anthropogenic impacts, including those of roads and traffic, on wildlife and protected areas is important and that speculative inferences should be avoided. However, we find Jackson et al.'s criticism largely unsubstantiated and affected by statistical misconceptions and errors. We comment on the key points made by Jackson et al. (2017) below.
Keywords: Carreteras; Impalas; Road ecology